Translation Analysis Of Deixis In Pasung Jiwa Novel Into Bound By Okky Madasari Muhammadiyah University Of Surakarta - Awalia, Diana; , Dr. Dwi Haryanti M. Hum (2016)
SUMMARY Diana Awalia. A 320 120 042. TRANSLATION ANALYSIS OF DEIXIS IN BOUND NOVEL INTO PASUNG JIWA BY OKKY MADASARI. Research Paper. School of Teacher Training and Education. Muhammadiyah University of Surakarta. 2016. This research focuses on deixis analysis used by the Bound novel into Pasung Jiwa by Okky Madasari and translation accuracy of Bound novel into Pasung Jiwa by Okky Madasari. This research is descriptive qualitative research. The purposes of this research are: (1) to describe the types and function of deixis analysis in Bound novel into Pasung Jiwa by Okky Madasari, (2) to describe the translation accuracy in Bound novel into Pasung Jiwa by Okky Madasari. The data of this research are utterances containing deictic word and translation accuracy collected from the data source. The data source is the Bound novel into Pasung Jiwa written by Okky Madasari. The methods of collecting data are documentation, questioner and interview. The results of this research show that there are 616 data. The researcher finds fifth deixis as follows: (1) 503 data belongs to person deixis, (2) 56 data belongs to place deixis, (3) 15 data belongs to time deixis, (4) 4 data belongs to social deixis, (5) 38 data belongs to discourse deixis. There are three aspects for good accuracy that analysis should fulfill: accurate, less accurate, and inacurate: (1) 200 data or 50 % accurately, (2) 155 data or 38,7 % less accurately, and (3) 42 data or 11, 3 % inaccurately. Keywords: novel, accuracy, deixis.